(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The tax base is one of the bases of the technical organizing of taxes, and that a good selection of the tax base effects the outcome of the tax and its fairness, and with the expansion of the tax range results a dangerous phenomenon called tax evasion, which became threaten the economies of countries and this phenomenon prevents the achievement of the state to its economic, political and social objectives which seeks to resolve this phenomenon and identifying all human and material potential and realize the real reasons that lie behind it. The researcher found that tax authorities are weak in terms of it the technical material and financial abilities, the analysis of data show that then is a significant reverse relation at the level of (%95) between tax justice and tax evasion, with a correlation coefficient%82.3). The more is tax justice, the less tax evasion and rise versa. The fair taxation accounts for (%68) of the changes in the tax evasion. The researcher recommend providing tax administrative with the required human resources and coping with administrative administrational and technological development in the process of taxation, The researcher also recommend adopting the important procedure for achieving tax justice to limit tax evasion.